2016
DOI: 10.1007/s00429-016-1250-9
|View full text |Cite
|
Sign up to set email alerts
|

The functional logic of corticostriatal connections

Abstract: Unidirectional connections from the cortex to the matrix of the corpus striatum initiate the cortico-basal ganglia (BG)-thalamocortical loop, thought to be important in momentary action selection and in longer-term fine tuning of behavioural repertoire; a discrete set of striatal compartments, striosomes, has the complementary role of registering or anticipating reward that shapes corticostriatal plasticity. Re-entrant signals traversing the cortico-BG loop impact predominantly frontal cortices, conveyed throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
79
0
15

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(101 citation statements)
references
References 235 publications
(469 reference statements)
3
79
0
15
Order By: Relevance
“…The reasons for the differences in neuronal recruitment between patterned and continuous stimulation, although interesting, are not the focus of this paper; methodological aspects perhaps involving a ChR2‐activated calcium conductance; reciprocal multisynaptic influences between direct and indirect SPNs and motor cortex (Burke et al., ; Freeze, Kravitz, Hammack, Berke, & Kreitzer, ; O'Hare et al., ; Oldenburg & Sabatini, ; Shipp, ), intrastriatal influences on SPNs (Planert, Szydlowski, Hjorth, Grillner, & Silberberg, ; Taverna, Ilijic, & Surmeier, ) and or the participation of interneurons (Damodaran, Evans, & Blackwell, ; Dehorter et al., ) should be considered in further analyses. Modulation of neuronal assemblies by specific patterns of neuronal stimulation may represent a modified animal model to study the pathogenesis in basal ganglia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reasons for the differences in neuronal recruitment between patterned and continuous stimulation, although interesting, are not the focus of this paper; methodological aspects perhaps involving a ChR2‐activated calcium conductance; reciprocal multisynaptic influences between direct and indirect SPNs and motor cortex (Burke et al., ; Freeze, Kravitz, Hammack, Berke, & Kreitzer, ; O'Hare et al., ; Oldenburg & Sabatini, ; Shipp, ), intrastriatal influences on SPNs (Planert, Szydlowski, Hjorth, Grillner, & Silberberg, ; Taverna, Ilijic, & Surmeier, ) and or the participation of interneurons (Damodaran, Evans, & Blackwell, ; Dehorter et al., ) should be considered in further analyses. Modulation of neuronal assemblies by specific patterns of neuronal stimulation may represent a modified animal model to study the pathogenesis in basal ganglia.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for the differences in neuronal recruitment between patterned and continuous stimulation, although interesting, are not the focus of this paper; methodological aspects perhaps involving a ChR2-activated calcium conductance; reciprocal multisynaptic influences between direct and indirect SPNs and motor cortex (Burke et al, 2017;Freeze, Kravitz, Hammack, Berke, & Kreitzer, 2013;O'Hare et al, 2016;Oldenburg & Sabatini, 2015;Shipp, 2017), intrastriatal F I G U R E 7 Analysis of network dynamics of D1 and D2 SPNs. The similarity index matrices of the stimulation induced by continuous (a) and stimulation in patterned pulses (b) show that continuous delivery of light activated sets of neurons with higher similarity index across stimulations, than stimulation delivered in patterned pulses.…”
Section: Discussionmentioning
confidence: 99%
“…Together, these examples demonstrate how laminar fMRI can be utilized to better characterize the nature of feedback effects from high-level respectively. The pulvinar is frequently implicated in attention, and shares feedforward and feedback connections with many regions throughout cortex (Shipp, 2003). This led Gouws et al…”
Section: Selective Attentionmentioning
confidence: 99%
“…This hypothesis can be tested using laminar fMRI, with the prediction that positive modulations originate in dorsolateral pulvinar, which projects primarily layers III and IV of occipital cortex (Shipp, 2003), while negative modulations originate in dorsomedial pulvinar, which projects primarily to parietal cortex (Behrens et al, 2003;Gutierrez et al, 2000)and then to feedback layers of visual cortex. Interestingly, one recent study found that increased neuronal firing rates from spatial attention were significantly stronger in input layer IV of macaque V4 compared to other layers (Nandy, Nassi, & Reynolds, 2017), providing some support for this hypothesis.…”
Section: Selective Attentionmentioning
confidence: 99%
“…When bored, people were willing to pay more for music -as though desperate for any stimulation to escape the boredom. Activity in the caudate nucleus -a subcortical structure known to be important for representing reward value [33] -was associated with decisions to avoid the boring task. Activity in the insula cortex was associated with just how willing people were to pay to avoid boredom -the higher your willingness to pay to avoid boredom the more activity was seen in the insula [32].…”
Section: Introductionmentioning
confidence: 99%